EFFECTIVENESS OF STUDENTS’ CORRECTIVE WORK WITH PRESCHOOL CHILDREN WITH COMPLICATED SPEECH DISORDERS - Perevorska Olena; Pryhodko Tetyana; Kobzіeva Iryna (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2019)
The paper deals with the problem of effectiveness of students’ corrective work with preschool children with complicated speech disorders. It is determined that this problem has become remarkably important, since the most complicated speech disorders remain one of the problems of psychophysical development of preschool age children. It is stated that the solution of the problem will be the introduction by students of the correction and development program named “Step by Step”, aimed at forming the speech competence in preschool children with complicated speech disorders. Students of the Dnipro National University named after Oles Gonchar under our leadership conducted a study of the level of speech competence formation in preschool children with complicated speech disorders in three stages. The study involved 32 children of older preschool age with complicated speech disorders divided into two groups (the experimental and control ones). The results of the study enabled the students to conclude that specially organized, systematic and regular correctional exercises on the speech competence formation in preschool children with complicated speech disorders are beneficial, as the number of children with high and moderate levels of speech development has increased. It means that there are positive changes in the level of speech competence formation in preschool children with complicated speech disorders. The obtained results testify to the effectiveness of correctional work of students with preschool children with complicated speech disorders.